One-Pot Synthesis of (Z)-β-Halovinyl Ketones via the Cascade of Sonogashira Coupling and Hydrohalogenation - Chen, Fa-Jie; Hua, Zhenguo; Chen, Jianhui; Chen, Jiajia; Lee, Daesung; Xia, Yuanzhi (Frontiers in Chemistry, 2021)
Herein, we report an efficient method for the synthesis of (Z)-β-halovinyl ketones through a one-pot Sonogashira coupling and hydrohalogenation reaction promoted by palladium-copper catalyst and Brønsted acid. The ynone intermediates are generated in situ from readily available acid chlorides and terminal alkynes at room temperature, which are directly converted to (Z)-β-halovinyl ketones by treating with triflic acid. This method avoids the use of an external halogen source and features broad substrate scope, high yield, and good to excellent stereoselectivity.